How to be a Bad Birdwatcher - Barnes, Simon (London Short Books, 2004)
Even the baddest birdwatcher in the world knows something about birds. Contrary to popular belief, you don't have to be an anoraked twitcher with top-of-the-range binoculars to have a good time admiring our often-neglected feathered friends in the sky.
Include Notes
Keywords: Bird Watching -- Barnes, Simon